Revised direct radiocarbon dating of the Vindija G1 Upper Paleolithic Neandertals - Higham, Tom (Array, 2006)
The 1998/1999 direct dating of two Neandertal specimens from level G1 of Vindija Cave in Croatia to approximately 28, 000 and 29, 000 radiocarbon (14C) years ago has led to interpretations concerning the late survival of Neandertals in south-central Europe, patterns of interaction between Neandertals and in-dispersing early modern humans in Europe, and complex biocultural scenarios for the earlier phases of the Upper Paleolithic. Using new methods, these Vindija G1 Neandertal fossils are redated to approximately 32, 000 – 33, 000 14C years ago and possibly earlier. These results highlight the importance of fine chronological control when studying this biocultural time period and the tenuous nature of monolithic scenarios for the establishment of modern humans and earlier phases of the Upper Paleolithic in Europe.